The sycamore lace bug Corythucha ciliata Say, 1832 (Hemiptera: Tingidae) — is a potentially dangerous invasive species in the phytocenoses of Kyiv - Borzykh, O.; Fedorenko, V.; Stryhun, O.; Chumak, P.; Vyhera, S.; Honcharenko, O.; Galagan, T.; Anol, O.; Kivel, Ie.; Tkachova, S. (Quarantine and plant protection, 2022)
Goal. To improve the methodology of effective phytosanitary monitoring of plane trees growing in botanical gardens, parks, garden squares and street plantings of Kyiv. Methods. Observations of the phytosanitary condition of plane trees were carried out by the method of route surveys in botanical gardens, parks, garden squares and street plantations in Kyiv (2019—2021). During the growing season, the lower side of the leaves and branches up to 1.5—2.0 m from the soil surface were inspected. Photographic equipment with the function of zooming in on the object (at least 10× «zooms») and subsequent computer processing was used to examine the leaves damaged by bedbugs on the treetops above. Results. Data on the degree of sycamore lace bug damage of plants in different localities of growth of plane trees in the megalopolis and the resistance of phytophagous to the extreme influence of abiotic environmental factors in this geographical area. Mass reproduction of bugs and significant damage to the leaves of plane trees we noted on the old plane trees on Holosiivskyi Avenue and Holosiivskyi Park named after M. Rylsky. Young plantations of plane trees (near the metro station «Exhibition Center», near the park named after M. Zankovetskoi and Velyka Vasylkivska Street) are damaged by lace bugs to a much lesser extent than the above-mentioned old ones. Survey of the collection of plane trees (Platanus occidentalis L., P. orientalis L., P. × acerifolia Ait., Willd.) in the Botanical Garden named after Acad. O.V. Fomina showed that no bug C.ciliata was found during all these years. In the National Botanical Garden named after M. Grishka of NAS of Ukraine the first damage to single leaves of the lower tier of plane trees was discovered only in September 2021 in the area of lilacs. Conclusions. For the first time in Kyiv, the invasive bug Corytucha ciliata Say was found on plane trees, and its distribution in botanical gardens, parks, squares and street plantings was also established. It should be considered that the primary source of penetration of the phytophage into the phytocenoses of the city was sycamore plants imported from nurseries of Europe. It was studied that on old plants under the bark in autumn, more than 80—90% of the total number of imago bugs can be found, and not a single one on young plants. This fact can be used to improve the system of protection of old and young plane trees from pests.